Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Semangat Kerja Karyawan Di CV.Puspa Agraria Malang - Fahmi, Kelvin Izza; Wahono, Budi; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine the effect of motivation and discipline factors on the work spirit of employees at CV Puspa Agraria, Malang Regency. This study uses a quantitative research method. The population in this study were employees at CV Puspa Agraria, Malang Regency, totaling 30. While the sample used the accidental sampling formula with a calculation result of 30 samples. The data used are secondary data and primary data using a questionnaire technique. The data analysis method used is instrument testing: validity reliability test, normality test, multiple linear regression analysis, hypothesis testing: simultaneous test, partial test and coefficient of determination.The results of the study indicate that simultaneously between the variables of work motivation and discipline factors on employee work spirit at CV Puspa Agraria have a significant effect on employee job satisfaction. Partially, the results obtained are that motivation factors do not have a significant effect on employee job satisfaction and work motivation has a significant effect on employee work spirit. Keywords : The Influence Of Work Motivation And Work Discipline On Employee Work Enthusiasm